Systematic Review on the Role of Health Administration, Nursing, and Social Work in Enhancing Patient Safety, Healthcare Quality, and Infection Control - Faten Abdulrazaq Alshallali; Tahani Talal Shukri; Amjad Othman Hassan Abdullah; Rola Ahmed Hadi Hakami; Ibtihaj Abdu Ahmed Mojammi; Hajar Muheel Almutairi; Haifa Bakur Abu Alula; Nouf Abdulrahman Turkustan; Mariam Khalid Alshugairi; Ahmed Mohammad M. Aljuhani; Mai Faraj Al-Ruhaili; Noura Abdulrahman Al-Ghamdi (International Journal of Medical Toxicology and Legal Medicine, 2025)
Patient safety, healthcare quality, and infection control are foundational pillars of modern healthcare systems and require coordinated, interdisciplinary efforts. This systematic review aims to explore the roles of health administration, nursing, and social work in promoting these core areas within hospital settings. A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, and Google Scholar for studies published between 2015 and 2024. Data were synthesized using a narrative approach due to heterogeneity in study designs. Findings revealed that health administrators contribute through institutional policy and leadership, nurses ensure clinical safety and infection control adherence, and social workers support psychosocial well-being and discharge planning. The integration of these disciplines was associated with reduced medical errors, improved patient satisfaction, enhanced infection prevention, and better care continuity. The review recommends adopting formal interdisciplinary frameworks in healthcare institutions to achieve safer and higher-quality outcomes.